1) S'il vous plait j'ai besoin d'aide pour ses expressions.
Développer et réduire:
A= x² +2x - 4 - 4 (2x + 3 ) - (x + 2) (x - 1)
B= (4x + 1) (7x - 2) - (5x - 8)²
C= (9x + 6) - (7x + 1)²
D= (14x - 9)² + (5x + 13)² - (11x + 6) (11x - 6)

1

Réponses

  • Utilisateur Brainly
2014-09-28T21:45:18+02:00
A= x² +2x - 4 - 4 (2x + 3 ) - (x + 2) (x - 1)
A= x² + 2x - 4 - 8x - 12 - (x² - x + 2x - 2)
A= x² - 5x - 16 - x² + x - 2x + 2
A= - 6x - 14

B= (4x + 1) (7x - 2) - (5x - 8)²
B= 28x² - 8x + 7x - 2 - (25x² - 80x + 64)
B= 28x² - x - 2 - 25x² + 80x - 64
B= 3x² + 79x - 66

C= (9x + 6) - (7x + 1)²
C= 9x + 6 - (49x² + 14x + 1)
C= 9x + 6 - 49x² - 14x - 1
C= - 49x² - 5x + 5

D= (14x - 9)² + (5x + 13)² - (11x + 6) (11x - 6)
D= 196x² - 252x + 81 + 25x² + 130x + 169 - (121x² - 36)
D= 221x² - 122x + 250 - 121x² + 36
D= 100x² - 122x + 286